Patterns and determinants of the global herbivorous mycobiome - Meili, Casey H; Jones, Adrienne L; Arreola, Alex X; Habel, Jeffrey; Pratt, Carrie J; Hanafy, Radwa A; Wang, Yan; Yassin, Aymen S; TagElDein, Moustafa A; Moon, Christina D; Janssen, Peter H; Shrestha, Mitesh; et al. (Nature communications, 2023)
Despite their role in host nutrition, the anaerobic gut fungal (AGF) component of the herbivorous gut microbiome remains poorly characterized. Here, to examine global patterns and determinants of AGF diversity, we generate and analyze an amplicon dataset from 661 fecal samples from 34 mammalian species, 9 families, and 6 continents. We identify 56 novel genera, greatly expanding AGF diversity beyond current estimates (31 genera and candidate genera). Community structure analysis indicates that host phylogenetic affiliation, not domestication status and biogeography, shapes the community rather than. Fungal-host associations are stronger and more specific in hindgut fermenters than in foregut fermenters. Transcriptomics-enabled phylogenomic and molecular clock analyses of 52 strains from 14 genera indicate that most genera with preferences for hindgut hosts evolved earlier (44-58 Mya) than those with preferences for foregut hosts (22-32 Mya). Our results greatly expand the documented scope of AGF diversity and provide an ecologically and evolutionary-grounded model to explain the observed patterns of AGF diversity in extant animal hosts.
Keywords: Digestive System; Biological Evolution; biologická evoluce; Feces; mykobiom; savci; Mycobiome; feces; Phylogeny; trávicí systém; Animals; zvířata; Mammals; fylogeneze